Cover Image. Issue 9 (17th November 2018) - Ranjit, Suman; Malacrida, Leonel; Gratton, Enrico
Abstract : On the cover: The cover image is based on the Research Article Differences between FLIM phasor analyses for data collected with the Becker and Hickl SPC830 card and with the FLIMbox card by Suman Ranjit et al., DOI:https://doi.org/10.1002/jemt.23061 .